THE RELATIONSHIP BETWEEN VITAMIN D LEVELS AND URIC ACID LEVELS IN THE ELDERLY AT SANTA ANNA NURSING HOME - Ester Elida O Harita; Felicia Kurniawan; Linawati Hananta; Isadora Gracia Sahusilawane (International Journal Labs, 2024)
As a person ages, the physiological function of the body decreases so that the risk of vitamin D deficiency and gout. The increasing elderly population can create a new era, namely the aging population. This study aims to see the relationship between vitamin D levels and uric acid levels in the elderly at Santa Anna Nursing Home. This study is an analytical observational study with a cross-sectional design with 70 elderly respondents living in Santa Anna Nursing Home, Jakarta. The correlation test is performed using the Pearson Correlation Test. There is a significant negative relationship between vitamin D levels and uric acid levels. In 23 elderly obtained average vitamin D levels of 36.9 + 8.4 ng / mL while high uric acid as many as 23 elderly (46%) with an average of 6.24 ± 1.9 mg / mL. From bivariate analysis, vitamin D levels were significantly associated with uric acid levels (r: -0.295, p: 0.037). There was a significant relationship between vitamin D levels and uric acid levels in the elderly at Santa Anna Nursing Home with a value of p = 0.041 (p < 0.05)